PERAN PENGEMBANGAN BISNIS DALAM MENINGKATKAN PENJUALAN: STUDI KASUS BOLU STIM MENARA KOTA MEDAN - Azzuhra, Syafrida; Riyanthi Br Sinuhaji, Ema Paska; Manalu, Yesaya Dandy; Triansyah, Fadli Agus; Lubis, Nurul Wardani (Politeknik Negeri Lhokseumawe, 2025)
Abstract: This study aims to analyze the role of business development in increasing sales within the local culinary industry, with a case study on Bolu Stim Menara in Medan. The background of this research stems from the intensifying competition in the local souvenir food industry, changing consumer preferences, and the need for companies to continuously innovate. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was reinforced through source and method triangulation. The findings indicate that the business development strategies of Bolu Stim Menara involve product innovation (local and contemporary flavor variations), distribution expansion (strategic outlets and partnerships), utilization of digital marketing (social media and influencers), and strengthening brand identity as a culinary icon of Medan. Product innovation plays a significant role in attracting new customers and enhancing loyalty among existing ones, while distribution and digital marketing increase accessibility and strengthen brand engagement. Key supporting factors include managerial vision, team creativity, and consumer loyalty, while challenges involve product quality consistency, intense competition, and seasonal raw material constraints. This study confirms that business development is not merely complementary, but a strategic instrument that determines sales sustainability and competitiveness. Theoretically, it enriches the business management literature on culinary business development strategies based on local wisdom. Practically, the findings provide valuable insights for similar businesses in formulating adaptive, innovative, and sustainable development strategies.Keywords: Business Development, Sales Improvement, Product Innovation, Distribution, Digital Marketing, Bolu Stim Menara.